Determination of annual organic carbon sequestration in soil and forest floor of Scots pine forests on The Türkmen Mountain (Eskişehir, Kütahya) - Şükrü Teoman Güner; Ender Makineci (İstanbul Üniversitesi Orman Fakültesi Dergisi, 2017)
This study was aimed to determine the annual organic carbon stocks in forest floor and soil in Scots pine (Pinus sylvestris L. subsp. hamata (Steven) Fomin.) forests. Research was conducted with two samplings in 2003 and 2013 on massive of Türkmen Mountains (Eskişehir, Kütahya) where located in West Central Anatolia Region in Turkey. Samplings were performed in 40 plots at pole (dbh=11.0-19.9 cm) and small tree (dbh=20.0-35.9 cm) development stages on different aspects, elevation, slope degree and slope positions. Data were evaluated with paired-samples t test. Soil organic carbon stocks show a significant (P<0.001) difference despite carbon stock in forest floor has not significant (P>0.05) difference between 2003 and 2013. Depending on these differences, accumulated carbon stocks were 2.88 Mg C ha-1 yr-1 in soil and 0.02 Mg C ha-1 yr-1 in forest floor.